Let your life speak : listening for the voice of vocation - Palmer, Parker J. (Jossey-Bass, 2000)
""Is the life I am living the same as the life that wants to live in me?" With this searching question, Parker Palmer begins an insightful and moving meditation on finding one's true calling. Let Your Life Speak is an openhearted gift to anyone who seeks to live authentically." "Sharing stories of frailty and strength, of darkness and light, Palmer shows that vocation is not a goal to be achieved but a gift to be received."--BOOK JACKET.